Fractographic Analysis of Strontium-Modified Al-Si Alloys - Hren, Iryna; Svobodova, Jaroslava (Manufacturing Technology Journal, 2018)
The research described in this contribution is focuses on fractographic analysis of the fracture area of AlSi7Mg0.3 alloy with modified strontium. Modification is an effective tool for improving the mechanical properties of aluminum alloys and affecting the microstructure of the material. The aim of the paper is to revise the microstructure of the modified AlSi7Mg0.3 alloy and to determine its strength properties. Within the experiment, the character of the refraction was evaluated and the presence of foreign particles and elements in the material fracture was monitored. Optical microscopy identified structural parameters of the castings just below the fracture surface as well as the course of the fracture line. Using a scanning electron microscope, the fracture area of the sample was analyzed, the EDS analysis was performed and the results of these analyzes were evaluated. An increased number of O, C and F elements occurred on the surface of the samples. The occurrence of these elements most likely results in a material breakage, which also confirms the results achieved by the static tensile test. On the basis of the obtained results from the analyzes carried out, the mechanisms of the breach were determined.
Keywords: AlSi7Mg0.3; modification; strontium; beryllium; microstructure